Efficiency and performance of Islamic banks in Bangladesh - Abduh, Muhamad; Hasan, Sidratul Mahabub; Pananjung, Alfatih Gesan (The International Association of Islamic Banks Karachi, 2013)
The aim of this study is to investigate the efficiency and performance of five Islamic banks in Bangladesh namely, Islami Bank Bangladesh Limited, Al- Arafah Islami Bank Limited, Social Islami Bank Limited, Shahjalal Islami Bank Limited and First Security Islami Bank Limited. Data are collected through their published annual reports from the year of 2006 to 2010. In addition, methods used to measure the performance and efficiency of Islamic banks are ratio analysis and data envelopment analysis respectively. With regard to banks’ performance, this study concludes that Shajalal Islami Bank limited is better than other Islamic banks in terms of its ROA, ROE, ETA, CAR, IER and AU ratios. On the other hand, with regard to banks’ efficiency, all Islamic banks have shown an improvement on their efficiency level. However, the result shows that First Security Islami Bank is better in terms of efficiency. This study complements other studies which discus about performance and efficiency in Islamic banks, particularly in the case of Bangladesh.